Cardiac Hypertrophy Is Inhibited by a Local Pool of cAMP Regulated by Phosphodiesterase 2. Issue 8 (25th September 2015) - Zoccarato, Anna; Surdo, Nicoletta C.; Aronsen, Jan M.; Fields, Laura A.; Mancuso, Luisa; Dodoni, Giuliano; Stangherlin, Alessandra; Livie, Craig; Jiang, He; Sin, Yuan Yan; Gesellchen, Frank; Terrin, Anna; et al.
<x xml:space="preserve">Abstract</x> Rationale: Chronic elevation of 3′-5′-cyclic adenosine monophosphate (cAMP) levels has been associated with cardiac remodeling and cardiac hypertrophy. However, enhancement of particular aspects of cAMP/protein kinase A signaling seems to be beneficial for the failing heart. cAMP is a pleiotropic second messenger with the ability to generate multiple functional outcomes in response to different extracellular stimuli with strict fidelity, a feature that relies on the spatial segregation of the cAMP pathway components in signaling microdomains. Objective: How individual cAMP microdomains affect cardiac pathophysiology remains largely to be established. The cAMP-degrading enzymes phosphodiesterases (PDEs) play a key role in shaping local changes in cAMP. Here we investigated the effect of specific inhibition of selected PDEs on cardiac myocyte hypertrophic growth. Methods and Results: Using pharmacological and genetic manipulation of PDE activity, we found that the rise in cAMP resulting from inhibition of PDE3 and PDE4 induces hypertrophy, whereas increasing cAMP levels via PDE2 inhibition is antihypertrophic. By real-time imaging of cAMP levels in intact myocytes and selective displacement of protein kinase A isoforms, we demonstrate that the antihypertrophic effect of PDE2 inhibition involves the generation of a local pool of cAMP and activation of a protein kinase A type II subset, leading to phosphorylation of the nuclear factor of activated T cells. Conclusions: Different cAMP pools have opposing effects on cardiac myocyte cell size. PDE2 emerges as a novel key regulator of cardiac hypertrophy in vitro and in vivo, and its inhibition may have therapeutic applications.